2014
DOI: 10.1155/2014/656325
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of a Hand Guided Robotic Drill for Cochleostomy

Abstract: The concept of a hand guided robotic drill has been inspired by an automated, arm supported robotic drill recently applied in clinical practice to produce cochleostomies without penetrating the endosteum ready for inserting cochlear electrodes. The smart tactile sensing scheme within the drill enables precise control of the state of interaction between tissues and tools in real-time. This paper reports development studies of the hand guided robotic drill where the same consistent outcomes, augmentation of surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In a comparison of manual versus robotic cochleostomy, there are significantly less intracochlear pressure disturbances using a robotic micro-drill (Assadi et al, 2013; Coulson et al, 2013; Dillon et al, 2016). A minimally traumatic cochleostomy can be achieved using an automatic or semi-automatic robotic drill, hand-guided robotic drill, or with laser (Brett et al, 2014; Hussong et al, 2008; Wimmer et al, 2014; Zhang et al, 2014). Robotic cochlear implant electrode insertion has also been validated in cadaveric models, demonstrating minimal insertion trauma and successful insertion in the majority of cases (McRackan et al, 2013; Schurzig et al, 2012; Venail et al, 2015).…”
Section: Translation Of Inner Ear Drug Delivery To Clinical Applicmentioning
confidence: 99%
“…In a comparison of manual versus robotic cochleostomy, there are significantly less intracochlear pressure disturbances using a robotic micro-drill (Assadi et al, 2013; Coulson et al, 2013; Dillon et al, 2016). A minimally traumatic cochleostomy can be achieved using an automatic or semi-automatic robotic drill, hand-guided robotic drill, or with laser (Brett et al, 2014; Hussong et al, 2008; Wimmer et al, 2014; Zhang et al, 2014). Robotic cochlear implant electrode insertion has also been validated in cadaveric models, demonstrating minimal insertion trauma and successful insertion in the majority of cases (McRackan et al, 2013; Schurzig et al, 2012; Venail et al, 2015).…”
Section: Translation Of Inner Ear Drug Delivery To Clinical Applicmentioning
confidence: 99%
“…Therefore, trauma may result from direct mechanical damage to the anatomy caused by the hand-guided tool or indirectly from the high induced sound pressure within the cochlea (17). Efforts have been made to provide a more consistent approach minimizing induced trauma on the hearing organ with the use of a force guided controlled tool or a robotic system (18)(19)(20)(21)(22)(23)(24). All of these developed approaches aimed for robust controlled penetration of the outer bone shell of the cochlea without penetration of the RWM.…”
Section: Introductionmentioning
confidence: 99%
“…During the operation of robotic technology in surgery, a high-level control loop needs to be closed at all times via the human observer using direct visual, microscopic or endoscopic inspection. Hence, performance of robot operation is limited to human sensing, processing and execution capabilities (Brett et al 2014) and as a result, the “super-human” sensing and actuation features inherent in robotic devices remain largely unharnessed in today’s Operating Rooms (ORs) (Marcus et al 2013). Next generation robotic devices will have to execute procedures reliably at geometric scales, temporal resolutions and safety levels beyond those possible for a human operator alone.…”
Section: Introductionmentioning
confidence: 99%
“…Research on RCI has so far focused on the individual elements of the procedure such as image-based strategy planning (Nobel et al 2012, Gerber et al 2014, Wimmer et al 2014a), guided keyhole trajectory drilling using surgical templates (Labadie et al 2005), industrial robotic manipulators (Federspil et al 2003, Xia et al 2008, Danilchenko et al 2011) and skull mounted passive kinematic structures (Kratchman et al 2011, Kobler et al 2015, Dillon et al 2015). Options for the reproducible creation of cochlear access using robotic force-feedback control (Brett et al 2014) and the design of robotic electrode insertion systems (Miroir et al 2012, Schurzig et al 2012) have been addressed. Zhang et al 2010 demonstrated the feasibility of deployment of steerable electrode arrays using robotic technology.…”
Section: Introductionmentioning
confidence: 99%